The Legislative Regulation of the Moral Barrier under Jordanian Law: A Comparative Study - Amer Mohammed Abdul-Kareem AL-Kharabsheh; Abdul-kareem OdttAllah Mohammed AL-Kharabsheh (International Journal of Law Research and Studies, 2026)
This study explores the moral barrier as one of the exceptions introduced by the Jordanian legislator within the rules of evidence, aiming to safeguard individual rights. The objective of this study is to clarify the concept of the moral barrier and define its legal framework by reviewing the relevant legal provisions and examining the position of the Jordanian legislator in comparison with certain Arab legislations. The study also addresses whether the instances of the moral barrier are exhaustively enumerated or merely illustrative. The study concludes with several findings, most notably that the Jordanian legislator has exhaustively defined the moral barrier. Accordingly, the study recommends amending paragraph (2) of Article (30) of the Jordanian Evidence Law to establish a general and absolute legal provision, thereby eliminating the restrictive enumeration of moral barriers currently in place.